Participation of Mothers in the Care of Premature Infants and its Associated Factors - Sharare Zabihi Afroozi; Seyedeh Noshaz Mirhaghjou; Sedigheh Pakseresht; Ehsan Kazem Nejad Leili; Zahiruddin Quazi Syed (Journal of Holistic Nursing and Midwifery)
Introduction: Parental participation in the care of and support to premature infants is the main factor in accelerating health improvement and growth of infants in the neonatal unit. Many factors are associated with this participation, whose investigation provides appropriate contexts for parental participation.